Identification of Albifimbria verrucaria (Myrothecium verrucaria) using new polyphasic taxonomy approaches - Syrchin, S.; Savchuk, Y.; Yurieva, O.; Tsyhanenko, K.; Pavlychenko, A. (Regulatory Mechanisms in Biosystems, 2024)
Filamentous fungus Myrothecium verrucaria UCM F-13522 (current name Albifimbria verrucaria) was isolated and identified by cultural and morphological characteristics, deposited in the Depositary of Microorganisms of the D.K. Zabolotny Institute of Microbiology and Virology of the NAS of Ukraine. Albifimbria verrucaria generally is a saprophytic fungus that belongs to the Stachybotryaceae family. A recent multigene analysis of the Stachybotriaceae family has allowed some species from the genus Myrothecium to be separated into a new introduced genus Albifimbria, and a species previously described as M. verrucaria has been named A. verrucaria as a typified representative. Accurate identification of Albifimbria verrucaria is of particular interest because of the wide range of its fungal activities. This species is ubiquitous plant-pathogenic fungus, cause of foliar spots in a large number of important crops and cultivated vegetables, and has exhibited bioherbicidal, nematicidal and antimalarial activities. Recently it was shown that A. verrucaria has become an opportunistic pathogen of humans. The aim of this work was to confirm the new taxonomic affiliation of the A. verrucaria strain UCM F-13522, for which we used a modern multilevel identification of the fungus with polyphasic taxonomy approaches. Cultural and morphological observations of the fungal mycelium confirm the previously described characteristics of A. verrucaria. The internal transcribed spacer (ITS) region of nuclear ribosomal DNA (rDNA) was used for DNA barcoding. Our research has shown that molecular identification with the ITS rDNA region is of sufficient variability to discriminate A. verrucaria from the species A. lateralis and A. terrestris. Comparison of ITS rDNA gene sequences revealed 3 different transition point mutations that distinguish A. lateralis and A. terrestris from A. verrucaria, at positions 51–52 and 54 nucleotides of the ITS2 region. The phylogenetic tree analysis based on ITS rDNA classified Albifimria spp. into a monophyletic clade, as in the multigene phylogeny. This indicates that it is possible to discriminate fungi of Albifimbria spp. using a single genetic marker. We studied the possibility of using the secondary structure model of the ITS rDNA region to identify Albifimbria spp. The set of the A. verrucaria verified culture collection strains and A. terrestris, A. viridis, A. lateralis type strains sequences were used fto construct a consensus model predicted minimum free energy secondary structures of the ITS2 region. An important characteristic in polyphasic taxonomy of fungi is the use of species-specific metabolites. Chemotaxonomic characters such as secondary metabolites and specific enzymes have not previously been used for taxonomic studies of Albifimbria genus. For chemotaxonomic identification, the bilirubin-oxidase (BOD) activity, unique to the Stachybotryaceae family, was used. Under submerged cultivation conditions A. verrucaria UCM F-13522 synthesized BOD with an activity of 3.6 units/mL. The enzymatic activity of BOD can be recommended as an important chemotaxonomic marker in A. verrucaria identification. Based on the culture, morphologic, molecular, and chemotaxonomic data obtained, the fungus Myrothecium verrucaria UCM F-13522 should be renamed Albifimbria verrucaria UCM F-13522. This study provides insight into the development of new species-specific markers for the discrimination of closely related to Albifimbria spp. by deploying polyphasic taxonomy approaches.